Unbalanced Voltage Detection with Measurement Analysis Current Signature (MCSA) in 3-Phase Induction Motor Using Fast Fourier Transform (FFT) - Widagdo, Reza Sarwo; Hermawati, Fajar Astuti; Hariadi, Balok (Electrical Engineering, Universitas Mercu Buana, 2024)
This paper presents a computational tool for detecting unbalanced voltage supplies in induction motors. For real-time applications, a technique based on the Fast Fourier Transform (FFT) was used to compute the desired component frequency. A Labview virtual instrument was used to implement the computer algorithm. When supply voltage unbalance appears identical, fault diagnosis using current signature analysis becomes more difficult. The detection percentage is calculated in the following conditions: balanced voltage, under voltage (10%), over voltage (5%), and mixed voltage (UV 5% + OV 5%). The unbalanced voltage waveforms are then analyzed using the classical Fast Fourier Transform (FFT). The results were detected at frequencies of 25 Hz and 75 Hz with a high amplitude of -30 db, when compared with healthy conditions at this frequency there was no spike in amplitude values. So by using the MCSA method with the fast Fourier transform approach analysis, it was successful in detecting voltage unbalance disturbances in 3 phase induction motors.